Dynamicity of the scout bee phase for an Artificial Bee Colony for optimized cluster head and network parameters for energy efficient sensor routing. (September 2018) - Shankar, Achyut; Jaisankar, N
Data transmitted to the base station from the sensor node by selecting an optimal cluster head is a massive challenge subjected to the routing protocol, in the case of the wireless sensor network. An energy efficient clustering method, depending on the Artificial Bee Colony (ABC) algorithm and the Fractional Artificial Bee Colony (FABC) algorithm, has a propensity to maximize the energy of the network and life time of nodes by the optimal cluster head selection (CHS). When conveying data, an ABC-Dynamic Scout bee algorithm is presented that multiplies the scout bee production to enlarge the number of alive nodes and the of CH energy. An assessment among the performances of the implemented ABC-based Dynamic Scout bee algorithm routing mechanism in opposition to that of ABC-based CHS and FABC-based CHS routing is done. The experimental outcome demonstrates that the implemented method increases the quantity of alive nodes with 25% of maximum energy for the normalized network compared with conventional protocols.